Toleransi Beragama Sebagai Pemicu Hak Berbudaya pada Masyarakat Heterogen - Ilim Abdul halim (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
Religious tolerance is an act of respecting or appreciating different religions based on mutual recognition of everyone's religious freedom. This paper aims to explain religious tolerance as pacemaker for cultural rights. The method used is a qualitative method using the theory of the function of religious tolerance as pacemaker cultural rights by Jurgen Habermas. The results showed that the existence of the Kampung Toleransi (tolerance village) led to several other villages establishing similar tolerance villages. Religious adherents have the same opportunity to exercise rights and freedoms that are actually distributed, use public means for the benefit of religious rituals, engage in religious celebrations and they have a collective identity. The conclusion shows that religious tolerance in the Kampung Toleransi (Tolerance Village) in Bandung City as pacemaker for cultural rights.